Haematological, biochemical and clinical signs changes following experimental infection of Streptococcus agalactiae in red hybrid tilapia (Oreochromis sp.) - Alsaid, Milud; F. Abuseliana, Ali; H. Daud, Hassan; M. Mustapha, Noordin; Bejo, Siti Khairani; M. Abdelhadi, Yasser; H. Hamdan, Ruhil (Aquacultura Indonesiana, 2014)
Hematological and biochemistry parameters are essential for the evaluation of fish health status; it helps provide essential information to diagnose fish diseases. This experiment was conducted to investigate the affect of Streptococcus agalactiae infection on hematological and biochemical parameters in red hybrid tilapia (Oreochromis sp.). The fish were inoculated intraperitoneally with 1 x104 cfu/mL bacteria then blood samples were collected and tested during the experiment. After seven days The red blood cell (RBC) counts decreased from 2.31 x 106to 1.68 x 106. The hemoglobin (Hb) and hematocrit (PCV) counts decreased to 7.17g/dl and 19.2% in the infected fish compared to the control group (9.71g/dl and 28.20%). In contrast, the white blood cell (WBC) counts increased from 4.20x103 in the control fish to 13.2x103. The biochemical results initially showed an increase in glucose levels of the infected fish compared to the control from 53.82 to 101.75 on the 72nd hour, respectively.  There were no significant differences in the levels of serum total protein (T. prot), albumin (ALB), and aspartate transminase (AST) between the infected and the control fish.The inoculated fish displayed marked clinical signs such as erratic swimming behavior, exophthalmia and lethargy during the experimental. The present study has established that the changes in hematological, biochemical and clinical signs of fish can be used as an early diagnosis of pathological and physiological status in red tilapia culture